VIRTUAL INTERACTIONS OF FAMILIES OF CHILDREN WITH CANCER: POTENTIAL SPACE FOR NURSE'S ACTIONS - Mattos, Camille Xavier de; Cabral, Ivone Evangelista (Cogitare Enfermagem, 2023)
Objective: to analyze nurses' resignification of the needs of family members of children with cancer in institutional Facebook® communities. Method: participatory research developed with the Speak Map and Body-Knowledge dynamics of the Sensitive Creative Method in Rio de Janeiro, Brazil, conducted between 2019 and 2020. Nine specialist nurses in pediatrics and oncology participated in groups of three to four people. Thematic analysis was applied in the treatment of the data. Results: dynamic virtual communities favor family members of children with cancer in the search for support, solidarity, and information. In that space, they share experiences of illness, successes, losses, and mourning. Challenges mark the community; the nurse can act as mediating information since prepared to interact with ethical responsibility and scientific knowledge. Conclusion: In the resignification, these communities are recognized as spaces for dialogue, expanding the locus of action and empowerment of nurse educators and advocates of the best interests of these children.